NONCONVENTIONAL TECHNIQUE TO MAKE BOROSILICATE GLASS FROTH - Lucian Paunescu; Sorin Mircea Axinte; Bogdan Valentin Paunescu (Nonconventional Technologies Review)
The article shows testing outcomes of preparing a froth from residual borosilicate bottle utilizing lignite coal powder as an expanding agent in association with water glass to avoid premature pre-oxidation of carbon before reaching the sintering temperature of the glass powder. The resulted froth had excellent heat-insulating properties, the apparent denseness and heat conductivity having low values ​​(0.35 g·cm-3 and 0.061 W·m-1·K-1, respectively). The compression resistance corresponding to the optimal version reached 2.6 MPa and the pore size interval was between 0.7-1.5 mm. In this experiment, the non-conventional electromagnetic wave heating technique was adopted and as an originality, a mixed heating method (partly direct and partly indirect) was chosen to keep safe the inner structure of the froth. The effectiveness of the method was demonstrated by the economic value of the energy consumption of the process (0.73 kWh·kg-1).